2000
DOI: 10.1073/pnas.97.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Coculturing diverse clonal populations prevents the early-stage neoplastic progression that occurs in the separate clones

Abstract: Most human cancers are of monoclonal origin and display many genetic alterations. In an effort to determine whether clonal expansion itself could account for the large number of genetic alterations, we compared spontaneous transformation in cloned and uncloned populations of NIH 3T3 cells. We have reported that progressive transformation of these cells, which is driven by the stress of prolonged contact inhibition at confluence, occurs far more frequently in cultures of recent monoclonal origin than in their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Lymphocytosis remained moderate over time (range 1460–6464/mm 3 ), possibly reflecting stabilization that regulates polyclonal proliferation. Recent studies have shown that mixing clonal populations strongly inhibits early‐stage neoplastic progression observed for isolated clones (17). This may also reflect a putative intrinsic protective mechanism activating spontaneous apoptosis when the tumour clone expands, as shown in recurrent cycling of a case of lymphoma (18).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytosis remained moderate over time (range 1460–6464/mm 3 ), possibly reflecting stabilization that regulates polyclonal proliferation. Recent studies have shown that mixing clonal populations strongly inhibits early‐stage neoplastic progression observed for isolated clones (17). This may also reflect a putative intrinsic protective mechanism activating spontaneous apoptosis when the tumour clone expands, as shown in recurrent cycling of a case of lymphoma (18).…”
Section: Discussionmentioning
confidence: 99%